2021
DOI: 10.1039/d1gc01670a
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of plant-specific alkaloids tetrahydroprotoberberines in engineered Escherichia coli

Abstract: Tetrahydroprotoberberines (THPBs), mainly sourced from the medicinal plants of genus Stephania and Corydalis, exhibit a variety of pharmacological activities. Plant-sourced THPBs are limited by low yields, and their chemical synthesis...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Moreover, when we diverted more carbon flux toward the branch point intermediate ( S )‐reticuline, the production of sanguinarine was only slightly increased (Figure 3b), indicating that reticuline oxidase (BBE) has become the bottleneck for sanguinarine biosynthesis in the engineered yeast strain (SAN006). Zhao et al found that BBE was mainly expressed as inclusion bodies in Escherichia coli and the functional expression level could be significantly increased by fusion expression with maltose binding protein and glutathione S‐transferase (W. Zhao et al, 2021). In addition to fusion expression with hydrophilic chaperons, we can also focus on searching for orthologous BBE candidates (X. Liu et al, 2017; Xu et al, 2021) or improving BBE activity via protein engineering to optimize the sanguinarine biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when we diverted more carbon flux toward the branch point intermediate ( S )‐reticuline, the production of sanguinarine was only slightly increased (Figure 3b), indicating that reticuline oxidase (BBE) has become the bottleneck for sanguinarine biosynthesis in the engineered yeast strain (SAN006). Zhao et al found that BBE was mainly expressed as inclusion bodies in Escherichia coli and the functional expression level could be significantly increased by fusion expression with maltose binding protein and glutathione S‐transferase (W. Zhao et al, 2021). In addition to fusion expression with hydrophilic chaperons, we can also focus on searching for orthologous BBE candidates (X. Liu et al, 2017; Xu et al, 2021) or improving BBE activity via protein engineering to optimize the sanguinarine biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the biocatalytic cascades could serve as interesting starting points for further improvement, such as adding methyltransferases, to synthesize methylated BIAs. 17…”
Section: Resultsmentioning
confidence: 99%
“…The conversions for (S)-14 and (S)-15 were lower than that of (S)-3 (90%). HPLC analysis showed that large amounts of styrenes (4-vinylguaiacol (16) and 4-vinylcatechol (17)) accumulated in the reaction mixtures (Fig. S4 †), and could be further converted to epoxides by StyAB.…”
Section: Expanding the Synthesis Of Bias From Dopamine And P-coumaric...mentioning
confidence: 99%
See 2 more Smart Citations